Theoretical studies of the optical and EPR spectra for VO²⁺ in Na₃C₆H₅O₇·2H₂O single crystal - Li, Ch.-Y.; Wang, G.-X.; Zheng, X.-M. (Condensed Matter Physics, 2015)
On the basis of the perturbation formulas for a d¹ configuration ion in a tetragonal crystal field, the three optical absorption bands and electron paramagnetic resonance (EPR) parameters (g factors gi and hyperfine structure constants Ai for i = || and ⊥, respectively) of VO²⁺ in Na₃C₆H₅O₇·2H₂O single crystals were studied using the perturbation theory method. By simulating the calculated optical and EPR spectra to the observed values, local structure parameters and negative signs of the hyperfine structure constants Ai of the octahedral (VO₆)⁸⁻ cluster in TSCD single crystal can be obtained. Базуючись на пертурбацiйних формулах для iону конфiгурацiї d
¹
у тетрагональному кристалiчному полi,
було дослiджено три смуги оптичного поглинання та параметри електронного парамагнiтного резонансу
(ЕПР) (g-фактори gi
та константи надтонкої структури Ai для i =∥ i ⊥, вiдповiдно) для VO²⁺ у монокристалах Na₃C₆H₅O₇·2H₂O, використовуючи метод теорiї збурень. Допасовуючи обчисленi оптичнi спектри
та спектри ЕПР до спостережуваних значень, можна отримати локальнi структурнi параметри та вiд’ємнi
знаки констант надтонкої структури Ai октаедричного кластера (VO₆)⁸⁻
8− в монокристалi тринатрiйцитрат
дигiдрату.